Extracorporeal Shock Wave Lithotripsy for Chronic Pancreatitis Patients With Stones After Pancreatic Surgery. Issue 5 (May 2018) - Wang, Dan; Ji, Jun-Tao; Xin, Lei; Bi, Ya-Wei; Pan, Jun; Liao, Zhuan; Du, Ting-Ting; Lin, Jin-Huan; Zhang, Di; Zeng, Xiang-Peng; Ye, Bo; Zou, Wen-Bin; et al.
Abstract : Objectives: The objective of this study was to evaluate the safety and efficacy of pancreatic extracorporeal shock wave lithotripsy (P-ESWL) in chronic pancreatitis (CP) patients with pancreatic stones after previous pancreatic surgery. Methods: This is a single-center study prospectively conducted in pained CP patients undergoing P-ESWL. Patients with a pancreatic surgery history (PSH) were included in the PSH group, and patients without a PSH during the same period were assigned to the control group. The primary outcomes included complications associated with P-ESWL and pain relief. Secondary outcomes included stone clearance and improved quality-of-life scores. Results: From March 2011 to October 2014, P-ESWLs were performed on 1017 patients (50 in the PSH group, 967 in the control group). No significant difference was observed in the frequency of occurrence of P-ESWL complications between the PSH group and control group (14.0% vs 13.2%, P = 0.877). At follow-up (2.6 years; range, 1.0–4.5 years), pain relief was achieved in 36 patients (75.0%), and 37 patients (77.1%) experienced complete stone clearance. No significant differences were observed between these patients and the matched controls. Conclusions: For CP patients who develop painful stones after pancreatic surgery, P-ESWL safely achieves significant pain relief and stone clearance, preventing the need for a repeat surgery. Abstract : Supplemental digital content is available in the text.